A functional model of responsive suspension-feeding and growth in bivalve shellfish, configured and validated for the scallop Chlamys farreri during culture in China - Hawkins, Anthony (2007)
A dynamic growth model is presented for the suspension-feeding scallop Chlamys farreri. The model is configured and validated for C. farreri cultured in Sungo Bay, China, using functional relations to simulate rapid and sensitive adjustments in feeding and metabolism as observed in response to the highly changeable environment there. Notable novel elements include resolving significant adjustments in the relative processing of living chlorophyll-rich phytoplankton organics, nonphytoplankton organics and the remaining inorganic matter during both differential retention on the gill and selective pre-ingestive rejection within pseudofaeces. We also include a facility to predict the energy content of non-phytoplankton organics. This is significant, for living phytoplankton contributed less than 20% towards suspended particulate organic matter within Sungo Bay. Further, the energy content of non-phytoplankton organics was very much more variable than for phytoplankton organics. Whether using that facility or assuming an average value for the energy content of non-phytoplankton organics, resolution of the relative processing of different particle types allows simulation of how the rates, organic compositions and energy contents of filtered, ingested and deposited matter change in response to differences in seawater temperature, seston availability and seston composition. Dependent relations predict rates of energy absorption, energy expenditure and excretion. By these means, our model replicates dynamic adjustments in feeding and metabolism across full ranges of relevant natural variability, and successfully simulates scallop growth from larvae or seed to harvestable size under different temporal and spatial scenarios of culture. This is an important advance compared with simpler models that do simulate responsive adjustments. Only by modelling the complex set of feedbacks, both positive and negative, whereby suspension feeding shellfish interact with ecosystem processes, can one realistically hope to assess environmental capacities for culture.